Dietary macronutrients and performance and plasma hormone and metabolite levels of broiler chickens fat by carbohydrate substitution - Malheiros, R. D.; Moraes, VMB; Collin, A.; Janssens, GPJ; Decuypere, E.; Buyse, J. (Eugen Ulmer Gmbh Co, 2004)
The present experiment was aimed to study the effects of an isocaloric substitution of fat by carbohydrate calories while maintaining the same CP content - on some endocrine parameters and key metabolites of the lipid (L), protein (CP) and carbohydrate (CHO) metabolism and muscle cell membrane integrity of broiler chickens. Ninety male broiler chicks (Cobb) were obtained at 1-day old and raised in an environmentally controlled room. Food and water was provided ad libitum. At day 7, the chicks were provided with the experimental diets: Control diet (CON: 20% CP; 9.1% L; 39.6% CHO), Low lipid diet (LowL: 22% CP; 3.36% L; 59.7% CHO), and low carbohydrate diet (LowCHO: 22% CP; 8.09% L; 46.7% CHO). T e chickens fed the CON manifested the best growth rate feed conversion compared to both other groups. The CO chickens showed the highest plasma T-3 Concentrations at 14 days of age as compared to both LowL and LowCHO chickens. At 35 days of age however, LowL chickens were characterized by the highest plasma T-3 levels. Overall, CON birds had the highest plasma T-4 levels (P < 0.0001) compared to LowL and LowCHO chickens. Plasma corticosterone levels were not affected by diet composition. Glucose levels increased towards the end of the experimental period, but there was no overall effect of diet composition on plasma glucose levels. Chickens fed the CON diet were consistently characterized by the highest plasma uric acid levels compared to LowL and LowCHO chickens. Irrespectively of diet, plasma triglyceride levels were high at 14 days of age, then decreased and finally increased again during the last week. This latter increase was most pronounced for the CON chickens and is congruous with their high fat deposition. At 28 days of age, a significant effect of diet was observed, as CON birds had lower plasma free fatty acid (FFA) levels compared to LowL but not to LowCHO chickens. However there was no overall effect of diet composition on plasma FFA levels. Creatine kinase (CK) activities increased significantly with age and were consistently higher in CON chickens. In conclusion, fast growth in broiler chickens is positively correlated with catabolism of protein from dietary or endogenous origin and (muscle) cell membrane disruption as reflected in high plasma uric acid levels and CK activity, respectively. The currently investigated substitution of fat by CHO had no marked effects on endocrine functioning and intermediary metabolism, but this does not exclude that larger substitutions between both nutrients can have an effect.
Keywords: broiler; macronutrients; blood metabolites; endocrine system; creatine kinase